Differentiation of leptospiral serovars by restriction endonucleases analysis - ELJALII Ι. Μ.; ALI, A. S. (Journal of the Hellenic Veterinary Medical Society, 2017)
DNA from ten leptospiral field isolates was digested with restriction enzymes, Hindlll, BamHl and EcoRl to differentiate leptospiral serovars. A high heterogeneity among the serovars examined was revealed. Similarities were observed among isolates of the same serovar. No relationship was found between the restriction patterns and the species from which the field strain was isolated. It appears that restriction endonucleases analysis would be useful in the differentiation of the leptospiral serovars.